Penetapan Kadar Kumarin dari Kulit Manis (Cinnamomum burmanii Bl.) dengan Metoda Kromatografi Gas - Yulianis, Yulianis; Adnan, Adek Zamrud; Putra, Deddi Prima (Fakultas Farmasi Universitas Andalas, 2011)
The qualitative and quantitative analysis of coumarin in cinnamon (Cinnamomum burmanii Bl.) which are qualified in to AA, KA and KB has been done by gas chromatography and gas chromatography-mass spectrometry. Extraction of quality KB coumarin was carried out by soxchletation in hexane, dichloromethane and methanol. Meanwhile, quality AA and KA coumarins are soxchletated in methanol. The qualitative analysis using gas chromatography-mass spectrometry with column BP-5 showed that hexane, dichloromethane and methanol extracts of qualified KB coumarin, as well as methanol extracts of qualified AA and KB only contain coumarin compounds, no other coumarin groups were found. From coumarin quantitative analysis by gas chromatography using BP-624 column and FID detector of methanol extracts obtained 1855.51 ppm (0.186%), 1915.75 ppm (0.192%), 9177.36 ppm (0,918%), for qualified KB, AA, and KA respectively.